2017
DOI: 10.1130/g38864.1
|View full text |Cite
|
Sign up to set email alerts
|

Defining the mechanism for compaction of the CV chondrite parent body

Abstract: 12The Allende meteorite, a relatively unaltered member of the CV carbonaceous 13 chondrite group, contains primitive crystallographic textures that can inform our 14 understanding of early Solar System planetary compaction. To test between models of 15 porosity reduction on the CV parent body, complex microstructures within ~0. deformation are consistent with brief heating events that were small in magnitude. When 28 combined with a lack of sintered grains and the spatially heterogeneous CPO, ubiquitous 29 hot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(64 citation statements)
references
References 19 publications
8
56
0
Order By: Relevance
“…This EBSD study is one of the first to focus on heavily metamorphosed (petrographic type 6) and presumably relatively "dry" ordinary chondrite meteorites, and as such contrasts with EBSD studies of weakly metamorphosed (type 3) and volatile-rich carbonaceous chondrites such as Allende (Watt et al, 2006;Forman et al, 2016Forman et al, , 2017. In the latter chondrites, grain size heterogeneity and water contents could have played a more important role during deformation (Bland et al, 2014;Davison et al, 2016;Tait et al, 2016).…”
Section: Introductionmentioning
confidence: 86%
“…This EBSD study is one of the first to focus on heavily metamorphosed (petrographic type 6) and presumably relatively "dry" ordinary chondrite meteorites, and as such contrasts with EBSD studies of weakly metamorphosed (type 3) and volatile-rich carbonaceous chondrites such as Allende (Watt et al, 2006;Forman et al, 2016Forman et al, , 2017. In the latter chondrites, grain size heterogeneity and water contents could have played a more important role during deformation (Bland et al, 2014;Davison et al, 2016;Tait et al, 2016).…”
Section: Introductionmentioning
confidence: 86%
“…; Forman et al. ; Krzesinska and Almeida ), or micro‐ and nanostructural details of minerals (e.g., Hanna et al. ; Ruzicka et al.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms are, in most cases, recorded in petrofabric (e.g., distribution of minerals), textural relationships of minerals (e.g., grain size distribution), and nanostructure (e.g., intracrystalline deformations). In the specific case of meteorites, the static metamorphism during accretion and impact-related processes operate under extremely different conditions; therefore, the mechanisms are usually well recorded in the highly contrasting textural relationships (e.g., Tomkins 2009;Tait et al 2014;Guignard and Toplis 2015;Krzesi nska 2017), fabric intensities (e.g., Gattacceca et al 2005;Friedrich 2008;Krzesi nska et al 2015;Forman et al 2017;Krzesinska and Almeida 2019), or micro-and nanostructural details of minerals (e.g., Hanna et al 2015;Ruzicka et al 2015;Ruzicka and Hugo 2018).…”
Section: Introductionmentioning
confidence: 99%
“…; Forman et al. , ) concluding that chondrule deformation and alignment occurs through impact‐induced reduction in matrix porosity through pore collapse with consequential matrix compaction. Silicate minerals within the deformed chondrules remain, however, unshocked or weakly shocked, thus justifying the classification of these chondrites at low shock levels of S1–S2.…”
Section: Introductionmentioning
confidence: 99%
“…Several structural studies of chondrites have identified deformed chondrules and grain alignment fabrics and have attributed these to burial (Cain et al 1986;Zolensky et al 1997) or shock impact (Scott et al 1992;Rubin and Swindle 2011;Lindgren et al 2015;Ruzicka and Hugo 2018); the latter seemingly in contrast with the low shock stage classifications (S1-S2) of many of the studied chondrites. This paradox is resolved by the results of matrix-based structural studies (Scott et al 1992;Nakamura et al 1995;Watt et al 2006;Forman et al 2016Forman et al , 2017 concluding that chondrule deformation and alignment occurs through impact-induced reduction in matrix porosity through pore collapse with consequential matrix compaction. Silicate minerals within the deformed chondrules remain, however, unshocked or weakly shocked, thus justifying the classification of these chondrites at low shock levels of S1-S2.…”
Section: Introductionmentioning
confidence: 99%